1986
DOI: 10.1021/ja00275a005
|View full text |Cite
|
Sign up to set email alerts
|

Low-temperature carbon-13 magnetic resonance in solids. 6. Methine carbons

Abstract: The low-temperature static solid 13C NMR spectra of the methine carbons of bicyclo[ 1.1.1] pentane, bicyclo-[l.l.l]pentanone, norbornadiene, cubane, trimethoxymethane, and isobutane were measured. Calculations of the shielding tensors by the individual gauge localized orbitals (IGLO) method were also performed for these compounds and for tetrahedrane. Assignments of the principal values to the molecular frame were made on the basis of these calculations for cases in which they were not determined by symmetry. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

1987
1987
2009
2009

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 1 publication
(8 reference statements)
1
14
0
Order By: Relevance
“…It is noted that bond contributions in the local bond frames become independent of the explicit molecular geometry, making a comparison in a series of molecules possible.11,28 This analysis has been used to analyze the 13C shielding tensors in methine and methyl carbons. 27,28 Semiempirical theories of chemical shielding are in general less successful than ab initio ones,41 but their simplicity and low computational cost make them appropriate for larger molecular systems for which current computational resources preclude the use of ab initio methods. In connection with the experimental work done in Utah, the very simple Pople model,55,56 using an MNDO wave function,57 has been used to rationalize the in-plane components of the 13C shielding tensors in pyrene.58…”
Section: Theoretical Methodsmentioning
confidence: 99%
“…It is noted that bond contributions in the local bond frames become independent of the explicit molecular geometry, making a comparison in a series of molecules possible.11,28 This analysis has been used to analyze the 13C shielding tensors in methine and methyl carbons. 27,28 Semiempirical theories of chemical shielding are in general less successful than ab initio ones,41 but their simplicity and low computational cost make them appropriate for larger molecular systems for which current computational resources preclude the use of ab initio methods. In connection with the experimental work done in Utah, the very simple Pople model,55,56 using an MNDO wave function,57 has been used to rationalize the in-plane components of the 13C shielding tensors in pyrene.58…”
Section: Theoretical Methodsmentioning
confidence: 99%
“…23 This is unlike most plastic crystalline phases which are frequently cubic. [25][26][27][28] The transition is a first order and associated with 5.4% increase in unit cell volume. [25][26][27][28] The transition is a first order and associated with 5.4% increase in unit cell volume.…”
Section: Introductionmentioning
confidence: 99%
“…Solid cubane undergoes a first‐order transition at 394 K from an orientationally ordered phase to a noncubic orientationally disordered (plastic) phase 4, 6–8. Although many studies have all shown evidence of this transition, the structure of the high‐temperature phase was not identified until recently.…”
Section: Introductionmentioning
confidence: 99%